New species, new records, and common species of Diderma (Physarales, Didymiaceae) from China - Xuefei Li; Yonglan Tuo; Jiajun Hu; You Li; Dan Dai; Frederick Leo Sossah; Jiajia Wang; Yanfang Guo; Shuyan Liu; Haixia Ma; Bo Zhang; Xiao Li; et al. (Microbiology Spectrum, 2025)
ABSTRACT Myxomycetes are fungus-like organisms that play a significant role in ecological processes, however, their taxonomic diversity and distribution in China are poorly understood. Diderma is an important genus within the Class Myxogastria that has received little attention in China. This study provides new insights into the geographic range of Diderma species in China and identifies previously unreported and newly recorded species. Our results reveal that the geographic distribution of Diderma species in China is more diverse than previously thought, with four previously unreported species found in Liaoning, Hubei, Sichuan, and Gansu provinces. In addition, we describe five new Diderma species that are distinct from previously known species, namely Diderma annuliferum, Diderma gansuense, Diderma roseum, Diderma jilinense, and Diderma flexocapillitium. We identified these species using a combination of morphological characterization, DNA sequencing, and phylogenetic analysis. Our findings have important implications for understanding Myxomycete biodiversity in China and can inform future research on the ecology, biogeography, and evolution of these fascinating organisms. Specifically, our study highlights the need for continued exploration of underrepresented areas to gain a more comprehensive understanding of the diversity and distribution of Myxomycetes in China.IMPORTANCEThe discovery of five new Diderma species and the revelation of their diverse distribution expand our understanding of Myxomycete diversity and provide a foundation for future studies on the ecology and biogeography of these organisms. These findings contribute to our knowledge of microbial diversity and have practical implications for conserving underrepresented areas and maintaining healthy ecosystems.